A case of langerhans cell histiocytosis associated with mantle cell lymphoma - Gül, Gülen; Özcan, Mehmet Ali; Demirkan, Fatih; Özkal, Sermin (Journal of Surgery and Medicine, 2018)
Langerhans Cell Histiocytosis (LCH), which is caused by neoplastic clonal proliferation of Langerhans cells, may be associated with various malignant neoplasms, especially lymphomas, in rare cases. In literature some studies observed an unexpected number of second malignancies, both prior to and after the diagnosis of MCL. Here, we report a case with concurrent LCH and mantle cell lymphoma (MCL) in a same lymph node. To the best of our knowledge, this is the second reported case of LCH associated with mantle cell lymphoma in a lymph node.